Reindeer husbandry and local planning - Niia, Lars P. (Rangifer, 1986)
A central theme in the reindeer husbandry is the conflicts between this and other economic interests as tourism, community development etc. in connection with the utilization of common territory. A retrospective glance will show that this is an old problem and not a new phenomenon. The Nordic Sami Institute has carried out a research project with the following objectives: 1.to give an account of the terms of planning for the reindeer husbandry, 2.to find out how the Såmi (Lapp) community's and so the reindeer husbandry's interests are taken into account in local planning. 3.find ways for how the reindeer husbandry's use of land can be described. 4.give suggestions as to how the interests of the Sami community can better be taken into account or how it can increase its influence in relation to planning. The suggestions based upon the results from the research project are: —that the Sami community aquire competence by preparing itself for the changes in its environment. —that it builds up its own organization. —that it aquires a more noticeable influence in community planning and decision making. This project and earlier experiencies have shown that the way of influencing e.g. by land-use-planning is weak and unreliable today. Renskötsel och kommunal planering. Abstract in Swedish / Sammandrag: Ett centralt tema i renskotselsammanhang ar konflikterna mellan renskotsel och andra ekonomiska intressen som turism, samhållsutbyggnad etc. vid utnyttjande av gemensamma arealer. En historisk tillbakablick visar att denna problematik inte på något sått år någon ny foreteelse utan ett gammalt tema med variationer i tid och rum. I ett forskningsprojekt vid Sami Instituhtta har en studie genomforts med syftet att: 1.soka beskriva planeringsforutsåttningarna for renskotseln. 2. soka forklara hur renskotselns intressen tas tillvara i den kommunala fysiska planeringen. 3. finna former for hur renskotselns markanvåndning kan beskrivas. 4. att låmna forslag på hur samebyns interessen kan båtre tillvaratas och hur den kan oka sitt inflytande i planeringssammanhang. På grundval av framkomna resultat foreslås: —att samebyn skapar egen kompetens. Det år fråga om att forbereda sig infor forandringar i omgivningen exvis i form av markanvåndnings- och utvecklingsplanering. —att samebyn bygger upp den egna organisationen. —att samebyn får ett mera breddat och fordjupat inflytande i det kommunala planerings- och beslutssystemet. Detta projekt och tidigare erfarenheter visar på att samråd som form for inflytande år svag och osåker. Poronhoito ja kunnallinen suunnittelu. Abstract in Finnish / Yhteenveto: Keskeinen teema poronhoidon yhteydesså on selkkaukset poronhoidon ja muiden taloudellisten hyotyjen vålillå kuten turismin, yhteiskunnan laajennuksen j.n.e. yhteisten pinta-alojen hyvåksikåytosså. Historiallinen, taannehtiva katsaus osoittaa, ettei tårna ongclma ole millåån tavalla joku uusi ilmio, vaan vanha teema vaihdellen ajassa ja alueilla. Sami Instituhttan erååsså tutkimusprojektissa on suoritettu tutkielma pitåen pååmåårånå: 1. koettaa kuvailla poronhoidon suunnitteluedellytykset, 2. koettaa selvittåå, miten poronhoidon edut otetaan talteen kunnallisessa, fyysilliscssa suunnittelussa, 3. loytåå ilmaisumuotoja siitå, miten poronhoidon maa-alueen kåytto voidaan kuvailla, 4. jåttåå ehdotuksia siitå, miten paliskunnan etuja voidaan paremmin ottaa talteen sckå miten se voi lisåtå vaikutusvaltaansa suunnittelun yhteydesså. Esilletulleiden tulosten perusteella ehdotetaan:— ettå paliskunta muodostaa oman toimivallan. On kysymys valmistautua ympåriston muutoksiin esimerkiksi maa-alueen kåyton- ja kehityssuunnittelussa, — ettå paliskunta perustaa oman jårjeston, — ettå paliskunta saa leveåmmån ja syvemmån vaikutusvallan kunnallisessa suunnittelu- ja pååtoselimesså. Tamd projekti ja aikaisempi kokemus osoittaa, ettå neuvottelu vaikutusvaltaisena on hcikkoa ja epåvarmaa.